1997
DOI: 10.1006/eesa.1997.1561
|View full text |Cite
|
Sign up to set email alerts
|

Metal Accumulation in Crayfish,Procambarus clarkii,Exposed to a Petroleum-Contaminated Bayou in Louisiana

Abstract: Red swamp crayfish (Procambarus clarkii) were placed for a period of 7 days in Bayou Trepagnier, a Louisiana waterway which received petroleum-laden effluents from a manufacturing complex several decades ago. However, coolant water from the plant continued to be released into the bayou until 1995. Analyses of sediments at the exposure site revealed heavy contamination by lead, chromium, and copper, while concentrations of arsenic and cadmium were very low. Significant bioaccumulation of lead was observed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 13 publications
6
28
0
Order By: Relevance
“…It is noteworthy that the hepatopancreas plays a central role in crustacean metabolism, accumulating and detoxifying a number of heavy metals (Rainbow and Scott 1979;Dall and Moriarty 1983). Anderson et al (1997) observed the formation of intracellular vacuoles in cells of hepatopancreas in response to heavy metal contamination. As confirmed by Coombs and George (1978), this is a mechanism utilized by hepatopancreas cells to sequester and detoxify metals.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the hepatopancreas plays a central role in crustacean metabolism, accumulating and detoxifying a number of heavy metals (Rainbow and Scott 1979;Dall and Moriarty 1983). Anderson et al (1997) observed the formation of intracellular vacuoles in cells of hepatopancreas in response to heavy metal contamination. As confirmed by Coombs and George (1978), this is a mechanism utilized by hepatopancreas cells to sequester and detoxify metals.…”
Section: Discussionmentioning
confidence: 99%
“…A metal that is mainly taken up from food is expected to become concentrated in the body tissues (FISHER and REINFELDER, 1995), or if the metals are taken up from solution they are absorbed onto exoskeleton (MIRAMAND and BENTLEY, 1992), although metals absorbed by water or trophic can be accumulated in the same organ. Indeed, water exposure leads to an accumulation in gills and in hepatopancreas (ANDERSON et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Data are available for lead, 15±17 cadmium, 15,17 aluminum, 15 iron, 16 copper 17 and mercury. 14,17 However, there is little information on the concentration of arsenic in this organism, 11 and there are no studies on the chemical speciation. Consequently, in addition to the ecological and socioeconomic aspects, special attention must be paid to the question of public health, since this is the raw material for various food products that are consumed in Spain and abroad.…”
mentioning
confidence: 98%